2013
DOI: 10.1002/hep.26186
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency is associated with hepatitis C virus chronic infection and with unresponsiveness to interferon-based antiviral therapy

Abstract: Recent data suggest that vitamin A modulates the expression of type I interferon receptor enhancing the antireplication effect of interferon-a on hepatitis C virus (HCV). This study aimed to investigate the prevalence of vitamin A deficiency among patients with chronic HCV infection and to assess whether vitamin A deficiency could be associated with unresponsiveness to interferon-based antiviral therapy. The analysis included 199 consecutive treatment-naïve chronic HCV patients in whom pretreatment serum vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…As quiescent stellate cells become activated, they lose their vitamin A stores and are then capable of producing collagen and subsequent fibrosis. Vitamin A deficiency has been reported in patients with hepatitis C-related chronic liver disease 21,22 and is associated with non-response to antiviral therapy. 22 Vitamin A deficiency is also present in approximately 50% of patients with alcoholic cirrhosis 21,23 and patients with chronic alcoholism have been shown to have very low concentrations of hepatic vitamin A at all stages of their disease.…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…As quiescent stellate cells become activated, they lose their vitamin A stores and are then capable of producing collagen and subsequent fibrosis. Vitamin A deficiency has been reported in patients with hepatitis C-related chronic liver disease 21,22 and is associated with non-response to antiviral therapy. 22 Vitamin A deficiency is also present in approximately 50% of patients with alcoholic cirrhosis 21,23 and patients with chronic alcoholism have been shown to have very low concentrations of hepatic vitamin A at all stages of their disease.…”
Section: Vitaminsmentioning
confidence: 99%
“…Vitamin A deficiency has been reported in patients with hepatitis C-related chronic liver disease 21,22 and is associated with non-response to antiviral therapy. 22 Vitamin A deficiency is also present in approximately 50% of patients with alcoholic cirrhosis 21,23 and patients with chronic alcoholism have been shown to have very low concentrations of hepatic vitamin A at all stages of their disease. 24 The presence of HE, a complex neuropsychiatric complication associated with liver disease, is associated with reduced serum retinol levels.…”
Section: Vitaminsmentioning
confidence: 99%
“…Retinol binding protein 4 transports 95% of serum retinol 37 and both parameters are strongly correlated (r = 0.884 in our study). Hence, the serum level of retinol strictly depends on the hepatic synthesis and excretion of RBP4, that, in turn, decreases in parallel to increasing liver damage 3840 and inflammation. 41 It has been suggested that a retinol-to-RBP4 ratio <0.8 reflects retinol deficiency better than serum retinol level.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, these studies were published by prestigious journals during consecutive years and provided independent and remarkable information, each of them including a different number of patients. Nevertheless, the significant association was lost if we reanalyzed it considering only one of these studies.…”
Section: Replymentioning
confidence: 99%